Reforms, Organizational Change and Performance in Higher Education 2019
DOI: 10.1007/978-3-030-11738-2_2
|View full text |Cite
|
Sign up to set email alerts
|

Performance in Higher Education Institutions and Its Variations in Nordic Policy

Abstract: The need for greater efficiency, productivity and quality in the higher education sector has triggered increased governmental interest towards different mechanisms of accountability, especially evaluation and performance measurement. This interest has developed over a relatively long period of time, but it has now reached its culmination point in many ways. For instance, advances in citation tracking, performance data collection and databases and the professionalisation of evaluative practices and methods have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 59 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…First, there has been a dramatic increase in the share of competition-based project funding on a national level. In fact, while project funding via various forms of research councils and other external funders made up some 30% before the reforms (while the rest was made up of direct funding from the government to the universities), it today makes up more than half of the total funding (Kivistö et al , 2019). And importantly, as this type of funding is based on ex ante assessments of called for or proposed research activities in which different research activities are set up against each other, this has arguably increased the overall competitive landscape for researchers in Sweden.…”
Section: Emergent Findingsmentioning
confidence: 99%
“…First, there has been a dramatic increase in the share of competition-based project funding on a national level. In fact, while project funding via various forms of research councils and other external funders made up some 30% before the reforms (while the rest was made up of direct funding from the government to the universities), it today makes up more than half of the total funding (Kivistö et al , 2019). And importantly, as this type of funding is based on ex ante assessments of called for or proposed research activities in which different research activities are set up against each other, this has arguably increased the overall competitive landscape for researchers in Sweden.…”
Section: Emergent Findingsmentioning
confidence: 99%
“…Perhaps the most evident of these include the global spread of the New Public Management doctrine (Hood, 1995; Miller et al , 1998; Pollitt and Bouckaert, 2004; Vakkuri, 2010); the growing public interest in international rankings and their effect on HEIs' competition for status, students and faculty (Czarniawska, 2019; Gebreiter and Hidayah, 2019; Mingers and Willmott, 2013; Northcott and Linacre, 2010; Pidd and Broadbent, 2015; Shore, 2008; Tourish et al , 2017; Tourish and Willmott, 2015); the growing importance of national and international accreditations (Ahrens and Khalifa, 2015; Alvesson et al , 2017; Czarniawska, 2019; Dobija et al , 2019); and increasing demands for transparency and accountability in higher education (e.g. Kivistö et al , 2019; Pinheiro et al , 2019). Moreover, one should not overlook the effect of public sector isomorphism, or in simpler terms, the tendency of public sector organizations to mimic each other and to copy practices from other sectors and countries (Kallio et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, the analysis of the literature revealed that the performance of HEIs relied importantly on IC initiatives that took place inside them (Paoloni et al, 2021 ; Singla et al, 2022 ; Guerrero et al, 2021 ; Vrontis et al, 2021 ; Cricelli et al, 2018 ). These initiatives significantly influence the performance of HEIs by reinforcing the increasing importance of scientific and technical production and diverse academic collaborations with stakeholders (Dezi et al, 2019 ; Kivistö et al, 2019 ; Guerrero et al, 2021 ; Cricelli et al, 2018 ).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%